A cross-sectional analysis of fall risk among institutionalized older adults in Malaysia - Zohari, Zahira; Rahim, Azliza; Mat Din, Hazwan; Saibul, Nurfaizah; Jafri, Asiah; Rahim, Shafikah; Nasir, Faizah; Sallehuddin, Hakimah (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Falls among older adults in institutional care are a significant concern due to their serious consequences and are further complicated by staffing constraints. Identification of key risk factors is essential for targeted prevention and closer monitoring. Objective: To identify the fall risk factors among older adults in institutional care and evaluate their relationships with overall fall risk. Methods: This retrospective cross-sectional study analyzed data from 184 residents of a public institutional care home in Selangor, Malaysia. Data were collected from January 2023 to October 2023 through fall risk assessments and medical records. A history of falls over the past 12 months was documented. Fall risk was assessed using the Downton Fall Risk Index (DFRI). Descriptive statistics were used to summarize participant characteristics and the prevalence of falls. Ordinal logistic regression was conducted to identify factors associated with higher fall risk scores. Results: The study included 184 participants (60.3% male), with the majority aged 70–79 years (45.4%). Common comorbidities were hypertension (50.5%) and diabetes mellitus (28.8%), with sensory impairments such as visual (50.0%) and hearing (32.1%) deficits. Polypharmacy was reported in 23% of participants, and almost a quarter had a history of falls. A high fall risk was observed in 39.7% of cases. Ordinal logistic regression revealed significant predictors of higher fall risk: hypertension (OR 5.93, 95% CI 2.18–16.14), polypharmacy (OR 5.53, 95% CI 2.11–14.47), visual impairment (OR 16.28, 95% CI 3.38–78.41), hearing impairment (OR 17.64, 95% CI 3.50–88.85), cognitive impairment (OR 33.12, 95% CI 4.61–237.88), psychiatric illness (OR 4.76, 95% CI 1.23–18.44), and female sex (OR 2.61, 95% CI 1.19–5.74). Conclusion: Regular fall risk assessments and tailored intervention plans that address these factors are crucial for reducing falls and improving the quality of life for this vulnerable population. These findings provide practical guidance for healthcare professionals, including nursing staff, in institutional care to prioritize high-risk residents and implement early preventive strategies. This article has been referred to by a Corrigendum: Belitung Nursing Journal, 2025, 11(6). https://doi.org/10.33546/bnj.4202.